From metabolic dysregulation to malignancy: the presence of ZPR1 in gastrointestinal and hepatopancreatobiliary malignancies - Chittilla, Mythri; Nagdev, Priyanka (Journal of Gastrointestinal Oncology, 2026)
Recent genetic studies have identified zinc finger protein one (ZPR1), specifically the rs964184 variant, as significantly associated with metabolic syndrome, dyslipidemia, hyperlipidemia, type 2 diabetes mellitus (T2DM), coronary artery disease (CAD), and metabolic dysfunction-associated steatotic liver disease (MASLD) across diverse populations. In addition to its metabolic associations, ZPR1 demonstrates altered expression patterns in several malignancies, including pancreatic adenocarcinoma (PAAD), esophageal squamous cell carcinoma (ESCC), and hepatocellular carcinoma (HCC). At the molecular level, ZPR1 contributes to lipid metabolism through interactions with epidermal growth factor receptor (EGFR) signaling and transcriptional activation of peroxisome proliferator-activated receptor gamma (PPAR-γ). Emerging evidence also suggests potential roles in tumor progression and cancer metabolism. This review summarizes the current understanding of ZPR1 in cell signaling, metabolic disease, and dyslipidemia and presents recent evidence of ZPR1 significantly expressed in gastrointestinal malignancies, while highlighting its potential relevance as a biomarker and therapeutic target in such. Further investigation into ZPR1 may advance understanding of cancer metabolism and support development of targeted precision medicine strategies.